2013
DOI: 10.1038/jid.2013.235
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin and Kit Signaling Sequentially Regulate Melanocyte Stem Cell Differentiation in UVB-Induced Epidermal Pigmentation

Abstract: UV radiation is a well-known inducer of epidermal pigmentation that is utilized in therapy for vitiligo, one of the skin depigmentation disorders. Although it has been reported that melanocyte stem cells (McSCs) play essential roles in hair pigmentation, the relationship between McSCs and epidermal pigmentation remains unclear. Repetitive UVB irradiation on the dorsal skin of F1 mice of HR-1 × HR/De caused apparent epidermal pigmentation, and it was characterized by increase in the number of melanocytes. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 28 publications
9
137
1
4
Order By: Relevance
“…SNA constructs are able to penetrate the stratum corneum of intact skin, rapidly enter epidermal and dermal cells, and knock down epidermal targets (17). In contrast to SNAs, other topical siRNAbased therapies require epidermal disruption by physical [e.g., injection, tape stripping (23), laser, or ultrasound] or chemical (e.g., conjugation to peptides or lipoplexes or incorporation into other types of nanoparticle structures, lentiviruses, or gels) means for RNAi penetration through the epidermal barrier and into KCs (24)(25)(26)(27)(28)(29)(30)(31). siRNA SNAs are unique, highly anionic constructs that do not require additional chemical modifications to facilitate transportation through the stratum corneum or entry into cells.…”
Section: Discussionmentioning
confidence: 99%
“…SNA constructs are able to penetrate the stratum corneum of intact skin, rapidly enter epidermal and dermal cells, and knock down epidermal targets (17). In contrast to SNAs, other topical siRNAbased therapies require epidermal disruption by physical [e.g., injection, tape stripping (23), laser, or ultrasound] or chemical (e.g., conjugation to peptides or lipoplexes or incorporation into other types of nanoparticle structures, lentiviruses, or gels) means for RNAi penetration through the epidermal barrier and into KCs (24)(25)(26)(27)(28)(29)(30)(31). siRNA SNAs are unique, highly anionic constructs that do not require additional chemical modifications to facilitate transportation through the stratum corneum or entry into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a separate study reported that epidermal keratinocytes and epidermal melanocytes secrete Wnt7 upon UVB exposure. Secreted Wnt7 was then responsible for melanocyte stem cell differentiation through the activation of Wnt/β-catenin signaling pathway [26]. Additionally, we have found that mROS were transiently increased upon 60 sec of laser treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Third and most important, it is also reasonable to speculate that the skin evolves multiple ways to protect organism from environmental insult [47]. For example, the UV radiation induces melanocytes differentiation to prevent the skin from injury [53]. Thus, under normal conditions, the neighboring epithelia-secreted factors further serve to enhance the quiescent state of melanocytes to prevent them from overdifferentiation.…”
Section: Discussionmentioning
confidence: 99%